2003
DOI: 10.1159/000075358
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients with Genetic Risk Factors of Pancreatitis: Impact on Treatment and Cancer Prevention

Abstract: Recent data suggest that genetic alterations are relevant risk factors for chronic pancreatitis. The highest risk is associated with autosomal-dominant mutations (N29I, R122H) of the cationic trypsinogen (PRSS1). Further mutations were identified in the genes of the pancreatic trypsin inhibitor (SPINK1) and in the cystic fibrosis transmembrane conductance regulator (CFTR). A remarkable finding was that both molecules were also mutated in patients suffering from alcoholic chronic pancreatitis. According to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Indeed, even though the clinical characteristics showed minor differences between groups, pancreatic cancers seems to be predominantly associated with mutations in the CFTR gene rather than in PRSS1, a gene more typically related to an increased risk for pancreatic cancer [31,35]. Even though it seemed to be lower than that reported in other series, the increased incidence ratio of pancreatic cancers we observed in our study is in agreement with that reported by other groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, even though the clinical characteristics showed minor differences between groups, pancreatic cancers seems to be predominantly associated with mutations in the CFTR gene rather than in PRSS1, a gene more typically related to an increased risk for pancreatic cancer [31,35]. Even though it seemed to be lower than that reported in other series, the increased incidence ratio of pancreatic cancers we observed in our study is in agreement with that reported by other groups.…”
Section: Discussionsupporting
confidence: 90%
“…Even though it seemed to be lower than that reported in other series, the increased incidence ratio of pancreatic cancers we observed in our study is in agreement with that reported by other groups. Indeed, a SIR of 67, which is more than twice as high as that observed in our work, has been reported in patients with PRSS1-associated hereditary pancreatitis [31], and a SIR of 53 has been recorded by the International Hereditary Pancreatitis Study Group [35]. The differences in the risk of cancer between our PRSS1 and CFTR cohorts seemed to be mainly related to smoking habits, male sex (more frequent in the CFTR group) and their older age during follow-up.…”
Section: Discussionsupporting
confidence: 61%
“…Some of these patients therefore consider prophylactic total pancreatectomy 98100. While this surgery will eliminate the patient’s very significant risk of developing pancreatic cancer, the benefit of prophylactic surgery has to be weighed against the real risks of total pancreatectomy 101.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…While this surgery will eliminate the patient’s very significant risk of developing pancreatic cancer, the benefit of prophylactic surgery has to be weighed against the real risks of total pancreatectomy 101. The main complication of total pancreatectomy is brittle diabetes and although there is now increasing experience in managing diabetes after total pancreatectomy, there is an increased risk of morbidity and mortality associated with this surgery 98, 99, 101103. Some have considered the option of islet autotransplantation, but the “cell of origin” for pancreatic cancer is not known, and the risk of autotransplanting a potential neoplastic cell remains a theoretical concern 98, 99, 101103.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%